Selective Sensitization to Penicillin V with Tolerance to Other Betalactams - Sánchez-Morillas, Leticia; Rojas-Pérez-Ezquerra, Patricia; González-Mendiola, Rosario; Gómez- Tembleque, Prado; Laguna-Martínez, Julio (Recent Patents on Inflammation & Allergy Drug Discovery, 2014)
Background: Penicillin G and V have the same betalactam ring. Penicillin V (phenoxymethylpenicillin) results from the substitution of the phenyl acetic acid of benzylpenicillin by the phenoxy methyl side chain. Methods: Our patient was a 34-year-old man who experienced generalized urticaria after ingestion of Penicillin V. We performed skin prick tests and intradermal tests with a battery of betalactams including Penicillin V. We also determined specific IgE against penicillin V, penicillin G, amoxicillin, and ampicillin and performed a single-blind oral challenge with Penicillin V, amoxicillin, cefuroxime, and ceftazidime. Results: The results of skin prick and intradermal tests with the betalactams included were negative. Specific IgE with betalactams was < 0.10 IU/L. The result of a single-blind oral challenge with Penicillin V was positive: 40 minutes after receiving 125mg of Penicillin V, the patient presented generalized pruritus with hives on his back and chest. He tolerated oral administration of amoxicillin, cefuroxime, and ceftazidime. Conclusion: We report an exceptional case of sensitization to Penicillin V with negative results in the allergy workup. Diagnosis was based on a positive single-blind oral challenge result. The patient tolerated other betalactams. We provide a brief summary of the most relevant recent patents.
Keywords: urticaria